Comparative analysis of numerical, evolutionary and metaheuristic methods for experimental implementation of selective harmonic elimination in a five-level emerging inverter - Naidji, M.; Toubal Maamar, A. E.; Boudour, M.; Garmat, A.; Aissa-Bokhtache, A. (Національний технічний університет "Харківський політехнічний інститут", 2026)
Multilevel inverters (MLIs) are widely used in renewable energy conversion and high-performance power applications due to their ability to generate output voltages with low harmonic distortion and reduced switching stress. Selective harmonic elimination (SHE) remains one of the most effective modulation strategies for suppressing low-order harmonics; however, its practical implementation relies on solving nonlinear transcendental equations that often require robust and efficient computational methods.

Багаторівневі інвертори (MLIs) широко використовуються в системах перетворення відновлюваної енергії та високопродуктивних енергетичних системах завдяки їхній здатності генерувати вихідну напругу з низьким рівнем гармонік та зменшеним напругою перемикання. Вибіркове усунення гармонік (SHE) залишається однією з найефективніших стратегій модуляції для зменшення гармонік нижчого порядку; однак її практична реалізація залежить від розв’язання нелінійних трансцендентних рівнянь, які часто вимагають надійних та ефективних обчислювальних методів.
Keywords: emerging multilevel inverter; genetic algorithm; Newton-Raphson algorithm; particle swarm optimization; selective harmonic elimination; новий багаторівневий інвертор; генетичний алгоритм; алгоритм Ньютона-Рафсона; вибіркове усунення гармонік; оптимізація рою частинок